KAJIAN AKTIVITAS ANTIOKSIDAN MIKROKAPSUL EKSTRAK KULIT TERONG UNGU (Solanum melongena L) - Efin Lestari; Ni Ketut Sumarni; Mappiratu Mappiratu (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Study about antioxidant activity of microcapsule of purple eggplant (Solanum melongena L) peel extract has ben done. The research aimed to find the best pH and coating ratio for yielding microcapsule with the highest antioxidant activity. It was done by applying 5 levels of both pH variation of 2, 3, 4, 5, 6 and maltodextrin ratio of 1:1, 2:1, 3:1, 4:1, 5:1 (w/v). The determination of antioxidant activity was done by DPPH method. The result showed that at pH 2 and 1:1 of maltodextrin coating ratio were the best condition to yield the highest antioxidant activity i.e 32.54 % and 96.31 %, respectively. Keywords: Purple eggplant peel, maltodextrin, microcapsule, antioxidant activity